(untitled) (Journal of the Asiatic Society of Bangladesh, Science, 2014)
Natural rubber is obtained almost from Hevea brasiliensis L. (family Euphorbiaceae). Rubber sheets are infected by fungi within 24 hours of processing and it is a major problem of rubber industry.The present research was undertaken to find out the mycoflora on rubber sheets and to devise a convenient method to protect the rubber sheets from fungal attack. The fungi were isolated from rubber sheets on PDA (Potato Dextrose Agar) medium. The isolated fungi were Aspergillus flavus Link, A. fumigatus Fresenius, A. niger van Tieghem, Cladosporium cladosporioidis (Fresen) De Vries, Corynespora cassiicola (Berk. & Curt.) Wei., Colletotrichum sp., Fusarium sp, Mucor sp., Penicillium sp. and Trichoderma viride Pers. Efficacy of common salt (NaCl) was evaluated against the isolated fungal species associated with unprocessed and processed rubber sheets in vitro. Radial colony growth of fungi associated with inocula prepared from unprocessed and processed rubber sheets was completely inhibited by salt at the concentrations used (10, 15 and 20 %) up to six months of observation. J. Asiat. Soc. Bangladesh, Sci. 40(1): 79-87, June 2014